2012
DOI: 10.1093/molehr/gas066
|View full text |Cite
|
Sign up to set email alerts
|

ART and health: clinical outcomes and insights on molecular mechanisms from rodent studies

Abstract: Since the birth of the first IVF-conceived child in 1978, the use of assisted reproductive technologies (ART) has grown dramatically, contributing to the successful birth of 5 million individuals worldwide. However, there are several reported associations of ART with pregnancy complications, such as low birthweight (LBW), preterm birth, birth defects, epigenetic disorders, cancer and poor metabolic health. Whether this is attributed to ART procedures or to the subset of the population seeking ART remains a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 168 publications
0
54
0
1
Order By: Relevance
“…In men with oligoasthenoteratozoospermia, methylation was markedly reduced at all CpGs, reaching statistical significance in subgroups with a sperm concentration of <10x10 6 /ml. These findings suggest that abnormal DNA methylation-mediated genomic imprinting is associated with oligoasthenoteratozoospermia and oligozoospermia (100)(101)(102)(103)(104)(105)(106)(107).…”
Section: Dna Methylation and Male Infertilitymentioning
confidence: 81%
“…In men with oligoasthenoteratozoospermia, methylation was markedly reduced at all CpGs, reaching statistical significance in subgroups with a sperm concentration of <10x10 6 /ml. These findings suggest that abnormal DNA methylation-mediated genomic imprinting is associated with oligoasthenoteratozoospermia and oligozoospermia (100)(101)(102)(103)(104)(105)(106)(107).…”
Section: Dna Methylation and Male Infertilitymentioning
confidence: 81%
“…Even with the successful implementation of these technologies, ART is associated with a number of complications, including a higher risk of congenital anomalies, hypertensive disorders of pregnancy, disorders of the placenta, preterm birth, low birth weight, perinatal mortality and small size for gestational age, imprinting disorders, among other problems presenting at birth, as well as later onset problems [58]. Animal models of ART with no underlying infertility, can exhibit analogous complications that have been described in ART children, suggesting that ART procedures are the source of these complications rather than reasons associated with infertility [9]. In this review, we discuss how ART procedures may impact epigenetic reprogramming coinciding with embryonic development and summarize the current epidemiological and experimental evidence suggesting ART procedures result in adverse postnatal cardiometabolic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Murine studies have indicated that the relatively transient nutritional stresses that IVF places on the growing embryo can result in a considerable change in gene expression, metabolism, and growth trajectory (8)(9)(10), persisting into adulthood (11)(12)(13)(14). Although the mechanisms are likely many, the increased incidence of random epigenetic errors, including changes in imprinted genes, has been proposed (10,15).…”
mentioning
confidence: 99%